Evaluation of tree measurements after the reconstruction of tree-row system in five narrow streets of Debrecen - André Zsiláné, Anikó; Zsila, László; Holb, Imre (Acta Agraria Debreceniensis, 2018)
Viable urban environment is largely dependent on the size, condition and distribution of urban green spaces within and around cities. Treerows in streets are one of the most essential elements of urban green spaces. The aim of this study was to evaluate tree taxa compositions and lifespan values of trees in tree-row system with special reference to five narrow streets (Garai, Jókai, Tanító, Csokonai and Zsák) of Debrecen. Tree numbers, tree taxa and the origin of tree taxa were determined in two years (2009 and 2017). As a next step, six selected taxa (Pyrus calleryana 'Chanticleer', Acer tataricum, Sorbus intermedia 'Browseri', Magnolia kobus, Acer platanoides 'Olmsted', and Crataegus x lavalleei 'Carrierei') were further estimated for the following lifespan parameters: i) trunk diameter (cm), ii) tree crown size (m), iii) trunk status (in 0–5 grades), iv) tree crown status (in 0–5 grades), v) estimated tree viability (in 0–5 grades), and vi) tree value in Ft. Our results showed that the numbers of tree taxa were 9 and 11 in 2009 and 2017 as well as an overall 279 and 282 trees were evaluated in 2009 and in 2017, respectively. More than 60% of the trees were native or similar to native taxa. The largest and the lowest trunk diameters were achieved for Pyrus calleryana 'Chanticleer' and for Acer tataricum, respectively. The largest and the lowest tree crown diameters were achieved for Acer platanoides ’Olmsted’ and for Magnolia kobus, respectively. The best and the worst trunk statuses by 2017 were achieved for Pyrus calleryana 'Chanticleer' and for Crataegus x lavalleei, respectively. The best and the worst tree crown statuses by 2017 were achieved for Pyrus calleryana 'Chanticleer' and for Acer tataricum, respectively. The best estimated tree viability status was achieved for Pyrus calleryana 'Chanticleer' and for Acer platanoides. Overall tree values were 2.73 times higher in 2017 compared to 2009. In conclusion, this study clearly demonstrated the importance of appropriate choice of tree taxa for an establishment of tree-row system in narrow street conditions.